(untitled) (Anclajes, 2025)
To think about relationship between the Common and the Singular in literary works is a complex activity. To study it, this article analyzes the 2017 novel Caja de fractales, by Puerto Rican writer Luis Othoniel Rosa, in order to identify the procedures that account for literature’s double common nature: at the same time, a collective use of a tradition, which belongs to everyone and no one, and the transindividual product resulting from the singular work of a "group individual". In Rosa’s case, special attention will be paid to procedures linked to the problems of intellectual property and its transgression, in the context of what the writer calls an "anarchist aesthetic" and what the Mexican writer Cristina Rivera Garza calls "poetics of disappropriation".